PENGELOLAAN TANAH KAS DESA PADA DESA BANJAR PANJANG KECAMATAN KERUMUTAN KABUPATEN PELALAWAN TAHUN 2001-2016 - Haryo Pratopo; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to determine the management of village cash land in the Village Banjar Panjang Kerumutan District Pelalawan District 2001-2016 and to determine the inhibiting factors in the management of village cash land in the Village Banjar Panjang Kerumutan District Pelalawan District 2001-2016. This research uses qualitative research method with descriptive research type which describes about problem and solving to research subject with clear and detail. This research found that the management of village cash land in Banjar Panjang Village Kerumutan sub district still run well, because the implementation still exists for personal interest by planting palm on the village treasury land, restan land, wakaf land and public facility land, so the village To get no income. The inhibiting factor is not optimal the management of village cash land in the village of Banjar Panjang Kerumutan District Pelalawan District, among them are: Human resources who lack expertise in the field of inventory of infrastructure assets insufficient in the affairs of asset management, not periodic inventasrisasi, budget Too large, unclear evidence of ownership of the village treasury, and poor supervision. The conclusion is that the planning, implementation and supervision of village cash management in Banjar Panjang Village Kerumutan Sub District still run well. Inhibiting factors in the management of village cash lands may impede the development of villages is lack of expertise. Human resources, periodic inventory, lack of budget, unclear evidence of ownership on village cash lands and lack of supervision. Keywords: Village Cash Land Management, Planning, Implementation, Supervision